Program Kemitraan Masyarakat Melalui Pemanfaatan Bioslurry Plus di Desa Montongsari Kabupaten Kendal Provinsi Jawa Tengah - Kusmiyati, Florentina; Herwibawa, B.; Yafizham, Yafizham (Seminar Nasional Lahan Suboptimal, 2018)
Kusmiyati et al, 2019. Community Partnership Program Through Utilization of Bioslurry Plus at Montongsari Village, Kendal Regency, Central Java Province. 138-145.Montongsari Village, Kendal Regency, Central Java Province has a biogas installation. Biogas waste, namely bioslurry, has not been used optimally. The activity aim   was to increase  knowledge and skills of farmers in bioslurry plus processing for crop cultivation. The method used were training, mentoring and  demonstration plots.   The participation of farmers was very high, as indicated by the presence and number of questions about bioslury plus. Assistance in producing bioslurry plus was done using a reactor from a 60 L plastic barrel. The materials used were 12 L bioslurry, 10 kg of  rock phosphate, 4 kg of wood charcoal and 4 kg of rotten fruit. The contents of nitrogen,  P2O5, K2O, C and C/N ratio of bioslurry plus  were 0.03%; 0.003%; 0.35%; 0.17% and 7.3 respectively.  The  demonstration plot was carried out to evaluate the efffects of bioslurry plus on growth and production of paddy cv. Inpari 32.  The results of demonstration plot showed that growth and production of  paddy at application of 5 % and 10 % bioslurry plus  were not significantly different from anorganic fertilizing treatment. The conclusion of this activity was  bioslury plus from biogas waste can be used as  organic fertilizer for paddy.